2014
DOI: 10.1111/1346-8138.12532
|View full text |Cite
|
Sign up to set email alerts
|

No association of atherosclerosis with digital ulcers in Japanese patients with systemic sclerosis: Evaluation of carotid intima‐media thickness and plaque characteristics

Abstract: Patients with systemic sclerosis (SSc) usually develop Raynaud's phenomenon, persistent digital ischemia and sometimes develop digital ulcers (DU). Several studies have reported an association of carotid artery atherosclerosis with SSc by evaluating carotid intima-media thickness (IMT) in SSc patients. However, none of those studies analyzed the association between DU and carotid artery atherosclerosis in SSc patients. We examined the association of carotid artery atherosclerosis with digital ulcers by compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

7
3

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Systemic scleroderma (SSc) is a generalized connective tissue disease characterized by fibrosis of the skin and internal organs, vascular dysfunction and immune disorder . Patients with SSc typically develop Raynaud's phenomenon (RP) and persistent digital ischemia, and often develop digital ulcers (DU).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic scleroderma (SSc) is a generalized connective tissue disease characterized by fibrosis of the skin and internal organs, vascular dysfunction and immune disorder . Patients with SSc typically develop Raynaud's phenomenon (RP) and persistent digital ischemia, and often develop digital ulcers (DU).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with SSc typically reveal RP and persistent digital ischemia and occasionally develop digital ulcers (DU) . We recently reported that the demographic and clinical features of the SSc patients with young age, male sex, anti‐topoisomerase I antibody positivity, severe skin sclerosis, interstitial lung disease complication and cardiac involvements are significantly more prevalent in patients with DU …”
Section: Introductionmentioning
confidence: 99%
“…The estimated incidence of LSc is 0.4–2.7 per 100 000 individuals, and the female‐to‐male ratio is 2.4 to 4.2:1 . The peak age for SSc onset is 35–55 years old, and it rarely develops in children and men younger than 35 years old . Our study suggests that young age might be a characteristic of SSc with LSc.…”
Section: Discussionmentioning
confidence: 64%